EFFECT OF MATURITY ON NUTRITIVE VALUE OF NATURAL PASTURE IN BUTANA, EASTERN SUDAN - Mahala, A.G.; FadelElseed, A.M.A.; L. Abdalla , (Journal of Veterinary Medicine and Animal Production, 2022)
Seventeen pasture grasses and forbs from Butana (eastern Sudan) during early (July 2007), and late (September 2007) season of rainfall, were evaluated in terms of chemical composition, mineral contents and in vitro gas production parameters. DM and CF contents were increased with maturity in both lower and upper limits of the range for the pasture grasses and forbs. In contrast, CP contents for both grasses and forbs species decreased with maturity. Forbs were ranked higher compared to grasses in respect of CP contents, while the opposite was occurred in terms of CF contents. According to CP contents at early stage the pasture, forbs and grasses species were ranked as follow: I.oblogfolia>C.olitorus>I.kordofana>R.patulla>A.viridis>P.bicolyata>B.erecta>T.terrestris>S.acromelaena>C.biflorus=C.rotundus> T.portulacastrum> D.muricata> D.annulatum> C.kotschyi> R.exltat> E.colonum. CP values were ranged from 8.77% to 23.15% at early stage, these values were ranged from very good to fair enough for animal feeding which may not need supplements, and from 4.94% to 20.28% at late stage from fair to poor which may need a protein supplement. Forbs accumulate more elements particularly Ca and Cu than grasses. All estimated elements are sufficient for animal requirement either in late or through out the season except Cu element. In most of pasture species the potential gas production decreased with maturity due to increase in structural carbohydrate particularly ADF. Accordingly, Butana pasture could be classified as good in term of CP content and elements (macro and micro) while it may need CP supplements at late season especially if grasses become dominant.